Commercialization of Waqf Assets in the Perspective of Legislation and Islamic Law - Muchlis Bahar (LEGAL BRIEF, 2022)
The purpose of this study is to analyze the problem of commercialization of waqf assets according to laws and regulations and Islamic law. This research uses qualitative research with descriptive analysis method. The type of data source used in this study is a secondary data source. Based on the results of the analysis, it can be concluded that according to the legislation in Article 1 paragraph (1) Government Regulation No. 28 of 1977 and Law No. 41 of 2004 concerning waqf as well as in the view of Islamic Law that commercializing waqf assets with the aim of obtaining profits that will be used to develop the waqf property itself is permissible (Mubah), because there is no evidence that forbids it. The results of this study also show that waqf assets may not be traded, therefore waqf assets are prohibited from being sold, donated and inherited, while producing waqf assets in the form of commercializing them is not prohibited